PENGARUH UMUR PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN MANUFAKTUR SUB MAKANAN DAN MINUMAN YANG TERDAPAT DI BURSA EFEK INDONESIA (BEI) PERIODE 2016– 2019 - Indra Saputra; - Rusmanto; Ilmiyatul Hikmah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
Abstract, This purpose of this research was to found whether effect Company Age and Company Size Against Corporate Social Responsibility (CSR) Disclosure In Food and Beverage Sub Manufacturing Companies on the Indonesia Stock Exchange (IDX) for the 2016–2019 Period. The sample drawn by purposive sampling and fulfill sample selection criteria. Method of data analysis using multiple linear regression. The results of the research show that the age and size variables partially or simultaneously have an effect on Corporate Social Responsibility (CSR). These results indicate that the age and size variables together affect the amount of Corporate Social Responsibility (CSR) for the investment made by investors. While R square, company age and company size affect the disclosure of Corporate Social Responsibility (CSR) by 86.8% and the rest is influenced by other variables or factors.